DOES INSTITUTIONAL OWNERSHIP AFFECT THE VALUE RELEVANCE OF ACCOUNTING INFORMATION? - Rizka Indri Arfianti; Prima Apriwenni; Martha Ayerza Esra; Elisabeth Vita Mutiarawati; Brenda Aurellia (Jurnal Ekonomi, 2023)
The purpose of this study was to find out whether the value relevance of the fair value of assets and liabilities at levels 1 and 2 is higher than at level 3 and to find out whether institutional ownership increases the value relevance of the fair value of assets at level 1, level 2 and level 3. This research was conducted in banking companies listed on the Indonesia Stock Exchange for the 2018-2020 period, which was determined using the purposive sampling method so that 90 company sample data were selected. Using the panel data linear regression method, the results show that the fair value of level 3 assets is more relevant than levels 1 and 2, while the fair value of liabilities at levels 1 and 2 produces a higher relevance than level 3. This research shows that it is not proven that level 1 and 2 fair value information is more relevant than level 3 for investor decision making. In subsequent tests, institutional ownership is not proven to increase the relevance of the fair value of level 1, level 2 and level 3 assets.